Caspase-1 deficiency reduces eosinophilia and interleukin-33 in an asthma exacerbation model. Issue 4 (16th October 2017) - Menzel, Mandy; Akbarshahi, Hamid; Mahmutovic Persson, Irma; Puthia, Manoj; Bjermer, Leif; Uller, Lena
Rhinovirus infections are common triggers of asthma exacerbations. Viruses can activate the inflammasome, resulting in processing and activation of caspase-1. This recruitment triggers production of interleukin (IL)-1β and IL-18, which have been implicated in asthma. Elucidating the involvement of the inflammasome and its compartments, such as caspase-1, in asthma exacerbations is warranted. Gene expression of caspase-1 was measured in rhinovirus-infected primary bronchial epithelial cells of asthmatic and healthy donors 24 h post-infection. In an in vivo exacerbation experiment C57BL/6 wild-type and caspase-1 -/- mice were challenged with house dust mite followed by exposures to the viral mimic poly(I:C). General lung inflammatory parameters and levels of T-helper type 2 (Th2)-upstream cytokines IL-33, thymic stromal lymphopoietin (TSLP) and IL-25 were assessed. Caspase-1 expression was elevated after rhinoviral infection exclusively in bronchial epithelial cells from asthmatics. In a translational mouse model of asthma exacerbation effects of caspase-1 on airway inflammation and Th2-upstream cytokines were explored. Caspase-1 deficient mice exhibited no alterations of general lung inflammatory parameters, but showed markedly reduced eosinophilia. Furthermore, the Th2-upstream cytokines IL-33, TSLP and IL-25 were reduced at exacerbation in mice lacking caspase-1. Rhinovirus infection increases bronchial epithelial caspase-1 in asthma. Caspase-1 may induce production of lung Th2-upstream cytokines and eosinophilia at exacerbations. Further targeting of caspase-1 signalling is warranted to explore its role in asthma exacerbations. Lack of caspase-1 reduces eosinophilia and expression of Th2-upstream cytokines at experimental asthma exacerbation http://ow.ly/NPMK30eMV2E